PARTISIPASI MASYARAKAT DAN ORANG TUA DALAM PENYELENGARAAN PENDIDIKAN - Sitti Roskina Mas (Fak. Tarbiyah UIN Maliki Malang, 2011)
Community and parents participation in education is to find out a theoretical bases on cummunity participation in education, relationship between schools and community, and community empowerment through school committee and education comission. The role of community through school committee and education commission have strateggies position to develop duty of community. School management climates are characterized by (1) school belonging attitude, (2) develop school policy, (3) develop quality of school conscoiusly, (4) pay attention to academic atmosphire, and (5) develop school operational standard.